Pengaruh Motivasi Investasi, Pengetahuan Investasi, dan Risk Perception Terhadap Minat Investasi di Pasar Modal Bagi Generasi Z : Survey Mahasiswa S1/D4 Akuntansi Angkatan 2020 PTN di Kota Bandar Lampung - Rahma Dhita Maharani; Endah Yuni Puspitasari; Arif Makhsun (CV. Ulil Albab Corp, 2024)
Investment in the capital market is crucial for a country's economic progress, yet the ratio of investors in Indonesia remains low. Generation Z holds significant potential as new investors. This study aims to examine the influence of investment motivation, investment knowledge, and risk perception on the investment interest of students in the capital market. The research method used is quantitative. The research uses a quantitative method, surveying 96 S1/D4 Accounting students from the 2020 cohort at a state university in Bandar Lampung, selected using Slovin's formula. Data were collected via questionnaires and analyzed using SPSS v26 software. The results show that investment motivation and risk perception positively influence investment interest, while investment knowledge does not. These findings highlight the importance of understanding the factors influencing Generation Z's investment interest to increase their participation in the capital market.